An X-band SiGe low-noise amplifier with high gain and low noise figure - Basyurt, Pinar Basak; Tarim, Nil (IEEE, 2008)
This paper presents the design of a low-noise amplifier (LNA) with high gain and low noise figure (NF), targeting the X-band, in 0.25 mum SiGe BiCMOS process provided by IHP. Simulation results show that at 10 GHz, the proposed LNA has a noise figure of 2.295 dB, with both input and output impedances matched to 50 Omega, an input return loss of -30.22 dB, an output return loss of -17.02 dB, and a voltage gain of 20.74 dB while dissipating 7.5 mW power from a 2.5 V power supply. The circuit occupies a chip area of 590 times 765 mum2.